ANALISIS STRATEGI BERSAING PT BANK SYARIAH BUKOPIN - , Ahmad Fadhil; , Dr. Tarsisius Hani Handoko, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to provide input to the Company in determining its competitive strategy which shall be done by (i) analyzing external environment using the five forces model to obtain factors of opportunity and threat to Company which ultimately enabling Company to determine factors of key success in its external environment, (ii) analyzing internal environment using value chain analysis method to determine competitive advantage of the Company and SWOT analysis method to determine strengths and weaknesses of the Company. Based on all of these analyses, Company may then determine its competitive strategy to improve Companyâs performance. Result of the five force analysis is as follows: (i) supplierâs bargaining position, high (ii) customer/buyer bargaining position, high (iii) threat of new competitor, high (iv) threat of substitute product, high (v) competition intensity, high. Result of SWOT analysis is as follows: (i) Strength: tight supervision, Multi Protocol Label Switch (MPLS) technology, strong financial and capital condition (ii) weakness: low capability of human resources, lack of aggressive marketing strategy, and low number of office branch (iii) Opportunity: strict and comprehensive regulation, increase of technology and increase of purchasing capability